2019
DOI: 10.4102/aveh.v78i1.495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of corneal biometry in a black South African population

Abstract: A thin CCT has been identified as an independent risk factor for the development of glaucoma, and many studies have shown that people of African descent have thinner corneas than people of European descent. 7 A study by Sardiwalla et al. 9 which looked at the CCT of about 200 South Africans demonstrated that black South Africans had a lower mean CCT compared to Indian South Africans (512.4 µm vs. 526.5 µm). These findings were consistent with what has been reported before in multicentre studies such as the Ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 34 , 35 Studies conducted in Nigeria and Africa at large have borne this out in studies quite similar to ours in which the authors reported that aging was associated with corneal thinning. 15 , 25 , 36 , 37 Although our study did not reveal significant clinical profiles that are typical of patients developing POAG that can be used as early indicators for the disease, apart from the usual monitoring of IOP, it is clear that individuals who require evaluation and management of glaucoma can be identified more readily through the provision of screening services and health education in communities, work, and religious institutions 38 so that patients at risk of glaucoma can be identified early and treated to avoid late presentation to the eye clinic with glaucoma and its associated complications.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 Studies conducted in Nigeria and Africa at large have borne this out in studies quite similar to ours in which the authors reported that aging was associated with corneal thinning. 15 , 25 , 36 , 37 Although our study did not reveal significant clinical profiles that are typical of patients developing POAG that can be used as early indicators for the disease, apart from the usual monitoring of IOP, it is clear that individuals who require evaluation and management of glaucoma can be identified more readily through the provision of screening services and health education in communities, work, and religious institutions 38 so that patients at risk of glaucoma can be identified early and treated to avoid late presentation to the eye clinic with glaucoma and its associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [ 12 ], studying an African population, authors did not find differences between sexes in astigmatism. The results of different studies are difficult to compare, due to the differences among them (ethnicity of the sample, sample size, measurement method).…”
Section: Introductionmentioning
confidence: 99%